2022
DOI: 10.1002/ppul.25848
|View full text |Cite
|
Sign up to set email alerts
|

Rho‐kinase inhibitors protect against neonatal hyperoxia‐induced airway hyperreactivity in a rat pup model: Role of prostaglandin F

Abstract: Background Oxygen therapy in preterm neonates is associated with airway hyperreactivity. The role of Rho/Rho‐kinase smooth muscle signaling in hyperoxia‐induced airway hyperreactivity remains understudied. We hypothesized that inhibition of Rho‐kinase will attenuate airway hyperreactivity induced by neonatal hyperoxia. Methods Newborn rats were raised in hyperoxia (>95% O2) or ambient air (AA) for 7 days. Subgroups were injected with a Rho‐kinase inhibitor: Y‐27632 (10 mg·kg−1·day−1) or fasudil (10 mg·kg−1·day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…14 Another study revealed that quercetin reduces myocardial Rho-kinase activity in rats, while in previous study we found that hyperoxia increases Rho-kinase expression and activity, and the administration of Rho-kinase inhibitors was protective against hyperoxia-induced airway hyperreactivity. 4,26 However, future studies are needed to undertake to clarify the involvement of quercetin on Rho/Rho-kinase signaling in its protective effect under hyperoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14 Another study revealed that quercetin reduces myocardial Rho-kinase activity in rats, while in previous study we found that hyperoxia increases Rho-kinase expression and activity, and the administration of Rho-kinase inhibitors was protective against hyperoxia-induced airway hyperreactivity. 4,26 However, future studies are needed to undertake to clarify the involvement of quercetin on Rho/Rho-kinase signaling in its protective effect under hyperoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Rings of 3 mm length were isolated from the mid-trachea and transferred into a tissue-organ bath containing KH buffer (10 mL) at 37°C, for in vitro force contraction measurements, as previously described. 4…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations